Genetic subtype classification using a simplified algorithm and mutational characteristics of diffuse large B‐cell lymphoma in a Japanese cohort. (10th August 2021) - Mishina, Tatsuzo; Oshima‐Hasegawa, Nagisa; Tsukamoto, Shokichi; Fukuyo, Masaki; Kageyama, Hajime; Muto, Tomoya; Mimura, Naoya; Rahmutulla, Bahityar; Nagai, Yurie; Kayamori, Kensuke; Hino, Yutaro; Mitsukawa, Shio; et al.
Summary: Recent large‐scale genetic studies have proposed a new genetic classification of diffuse large B‐cell lymphoma (DLBCL), which is clinically and biologically heterogeneous. However, the classification methods were complicated to be introduced into clinical practice. Here we retrospectively evaluated the mutational status and copy number changes of 144 genes in 177 Japanese patients with DLBCL, using targeted DNA sequencing. We developed a simplified algorithm for classifying four genetic subtypes—MYD88, NOTCH2, BCL2, and SGK1—by assessing alterations in 18 representative genes and BCL2 and BCL6 rearrangement status, integrating the significant genes from previous studies. In our cohort and another validation cohort from published data, the classification results in our algorithm showed close agreement with the other established algorithm. A differential prognosis among the four groups was observed. The NOTCH2 group showed a particularly poorer outcome than similar groups in previous reports. Furthermore, our study revealed unreported genetic features in the DLBCL subtypes that are mainly reported in Japanese patients, such as CD5‐positive DLBCL and methotrexate‐associated lymphoproliferative disorders. These results indicate the utility of our simplified method for DLBCL genetic subtype classification, which can facilitate the optimisation of treatment strategies. In addition, our study highlights the genetic features of Japanese patients with DLBCL.